EFFECT OF LEVELS OF SALINITY IRRIGATION WATER AND SPRAYING AMINO ACIDS ( PROLINE، ARGININE) IN THE GROWTH AND HOLDS POTATO Solanum. tuberosum L. - Rashid, Zeina S.; Mohammed, Mohammed S.; Al-Gawoshe, Shehab A. (Diyala Agricultural Sciences Journal, 2017)
The experiment in the field of Scholastic in the province of Diyala-Mandali hand for the Fall 2014 season and which planted the potato Solanum tuberosum L. Cv. Riviera class Elite has been aimed experiment to see the effect of the level of irrigation water used and the amino acids added and the method of addition and interaction in recipes vegetative growth and winning the potato. Experience has included the effect of three levels of irrigation water salinity (2, 3.6 and 5.1) ds m-1 and has a drip irrigation in a way, and added amino acid Proline, Arginine and two levels of 0 and 200 p p m and sprayed in two ways and under plant. The experiment carried out according to the design of a skateboard dissident Split Plot as represented salinity levels of irrigation water under the President the amino acids in the main concentrations below under three replicates has been tested differences between the averages by test LSD at the 5% level of probability. The results can be summarized as follows:- 1- Increased salinity of irrigation water from 2 to 5.1 ds m-1 to reduce plant height and total chlorophyll and quotient total and quotient the marketable. 2- Marked by spray treatment Proline a concentration of 200 p p m and interfere with irrigation water salinity 2 ds m-1 to give the plant's highest and the highest total chlorophyll concentration and largest quotient holistic and holds a marketable compared to other interactions